Composition dependent electrocaloric behavior of (SrxBa1-x)Nb2O6 ceramics. Issue 168 (2nd January 2016) - Singh, V. P.; Patel, Satyanarayan; Vaish, Rahul
ABSTRACT: This article presents electrocaloric effect in (Srx Ba1-x )Nb2 O6 ceramics (where x = 0.25, 0.50 and 0.75) using an indirect approach based on Maxwell's relations. Here, we have calculated various parameters of electrocaloric effect like temperature change ( ΔT ), entropy change ( ΔS ) and heat carrying capacity ( ΔQ ) of material due to the change in polarization under two different electric fields of 30 kV/cm and 20 kV/cm. (Srx Ba1-x )Nb2 O6 ceramics is well known pyroelectric material, where by increasing Sr/Ba ratio the ferroelectric behavior turns towards relaxor behavior. While in terms of electrocaloric effect performance (temperature change ΔT ) is increase as the Sr/Ba ratio increases. Additionally, maximum ΔT (0.30 K) was found for (Srx Ba1-x )Nb2 O6 ceramic having x=0.75 molar concentration under the electric fields of 30 kV/cm.